2008
DOI: 10.1037/0012-1649.44.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination and psychological distress: The impact of ethnic identity and age among immigrant and United States-born Asian adults.

Abstract: The association between racial and ethnic discrimination and psychological distress was examined among 2,047 Asians (18 to 75 years of age) in the National Latino and Asian American Study, the first-ever nationally representative study of mental health among Asians living in the United States. Stratifying the sample by age in years (i.e., 18 to 30, 31 to 40, 41 to 50, 51 to 75) and nativity status (i.e., immigrant vs. U.S.-born), ethnic identity was tested as either a protective or exacerbating factor. Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
388
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 387 publications
(425 citation statements)
references
References 88 publications
31
388
5
1
Order By: Relevance
“…The impacts of this ethnic stigmatisation include a loss of self-esteem and a lower access to the social resources that contribute to the health and psychological well-being of individuals, such as adequate housing, income and employment. Discrimination has been shown to be a risk factor for psychological distress in several studies (Gonzalez-Castro andUbillos 2011, Yip, Gee, andTakeuchi 2008). Findings from the study carried by Thapa and Hauff (Thapa and Hauff 2005) suggest that women and men may react differently to specific manifestations of discrimination: the mean level of distress was higher in men who were denied a job whereas it was higher in women who were denied housing.…”
Section: Socio-demographic Factorsmentioning
confidence: 51%
See 1 more Smart Citation
“…The impacts of this ethnic stigmatisation include a loss of self-esteem and a lower access to the social resources that contribute to the health and psychological well-being of individuals, such as adequate housing, income and employment. Discrimination has been shown to be a risk factor for psychological distress in several studies (Gonzalez-Castro andUbillos 2011, Yip, Gee, andTakeuchi 2008). Findings from the study carried by Thapa and Hauff (Thapa and Hauff 2005) suggest that women and men may react differently to specific manifestations of discrimination: the mean level of distress was higher in men who were denied a job whereas it was higher in women who were denied housing.…”
Section: Socio-demographic Factorsmentioning
confidence: 51%
“…In general, immigrant women report a higher mean level of distress than immigrant men (Gonzalez-Castro and Ubillos 2011, Lerner, Kertes, andZilber 2005, Levecque, Lodewyckx, andBracke 2009) although this www.intechopen.com difference may not be statistically significant in older immigrants (Chou 2007, Ritsner, Ponizovsky, andGinath 1999). Similarly, financial hardship (Gonzalez-Castro and Ubillos 2011, Lerner, Kertes, andZilber 2005, Sundquist et al 2000), poor self-reported health (Chou 2007, Lerner, Kertes, andZilber 2005) and recent stressful events (Lerner, Kertes, andZilber 2005, Thapa andHauff 2005) act as risk factors whereas family cohesion (Lerner, Kertes, andZilber 2005, Yip, Gee, andTakeuchi 2008) and the sense of control over one's life (Lerner, Kertes, andZilber 2005, Sundquist et al 2000) play a protective role. The influence of other long-established risk and protective factors is more uncertain.…”
Section: In Immigrantsmentioning
confidence: 99%
“…The accumulation of these seemingly petty encounters can be a chronic stressor that erodes Asian Americans' coping resources and abilities, subsequently affecting their overall well-being. Indeed, available research findings have indicated the adverse effects of racism influence every aspect of Asian Americans' lives, including their physical and mental health outcomes and rates of substance abuse (Ahmed, Mohammed, & Williams, 2007;Brondolo, Gallo, & Myers, 2009;Chae, Takeuchi, Barbeau, Bennett, Lindsey, Stoddard, et al, 2008;Evans-Campbell, Lincoln, & Takeuchi, 2007;Gee et al, 2009;Kim et al, 2012;Liang et al, 2010;Okazaki, 2009;Spencer, Chen, Gee, Fabian, & Takeuchi, 2010;Yip et al, 2008). However, a plausible alternative explanation is that experiencing more RDEs leads to greater critical ethnic awareness of the social injustices regularly endured by Asian Americans.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research indicated many sociodemographic factors can influence the relationship between discrimination and well-being (e.g., Alvarez & Juang, 2010;Yip et al, 2008). Preliminary analyses were performed to examine whether any significant differences existed between demographics (age, sex, education, and nativity status) and the variables of interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation